The Kjeldahl method for organic nitrogen - Bradstreet, R. B. (Raymond B.) (Academic Press, 1965)
The Kjeldahl Method for Organic Nitrogen volume presents a broad and comprehensive survey of the method as applied to natural products and organic nitrogen compounds. The quantitative determination of an element as widely distributed as nitrogen is of great importance, and the truth of this is borne out by the tremendous amount of literature published throughout the years. The analysis of nitrogen can be divided into two classes: inorganic and organic. This book is concerned only with organic nitrogen compounds, and specifically their determination by the Kjeldahl method. The book opens with a chapter on the historical background and the work leading to the evolution of the method. This is followed by separate chapters that discuss each of the several divisions of the method, e.g., salt addition, reduction, oxidation, catalysts, distillation.